Proximity of the home to roads and the risk of wheeze in an Ethiopian population. Issue 6 (18th May 2005) - Venn, A; Yemaneberhan, H; Lewis, S; Parry, E; Britton, J
Abstract : Background: There is widespread public concern that exposure to road vehicle traffic pollution causes asthma, but epidemiological studies in developed countries have not generally confirmed a strong effect and may have underestimated the risk as a result of relatively high and widespread exposure to traffic in everyday life. Aims: To investigate the effect of living close to a traffic bearing road on the risk of wheezing in Jimma, Ethiopia where road traffic is generally low and restricted to a limited network of roads. Methods: Data have been previously collected on respiratory symptoms, allergic sensitisation, and numerous demographic and lifestyle factors in a systematic sample of inhabitants of Jimma town. In 2003 the homes of these people were retraced; the shortest distance to the nearest surfaced road, and traffic flows on these roads were measured. Results: Distance measurements were collected for 7609 (80%) individuals. The overall prevalence of wheeze was similar in those living within 150 m of a road compared to those living further away (3.9% v 3.7%), but among the 3592 individuals living within 150 m, the risk of wheeze increased significantly in linear relation to proximity to the road (adjusted odds ratio = 1.17 per 30 m proximity, 95% CI 1.01 to 1.36). This relation was stronger, though not significantly so, for roads with above median traffic flows. Conclusion: These findings indicate that living in close proximity to road vehicle traffic is associated with an increased risk of wheeze, but that other environmental factors are also likely to be important.